2017
DOI: 10.1126/science.aal2380
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic plasticity and the hallmarks of cancer

Abstract: Chromatin and associated epigenetic mechanisms stabilize gene expression and cellular states, while also facilitating appropriate responses to developmental or environmental cues. Genetic, environmental or metabolic insults can induce overly restrictive or overly permissive epigenetic landscapes that contribute to pathogenesis of cancer and other diseases. Restrictive chromatin states may prevent appropriate induction of tumor suppressor programs or block differentiation. By contrast, permissive or ‘plastic’ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
850
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,059 publications
(869 citation statements)
references
References 116 publications
(142 reference statements)
12
850
1
6
Order By: Relevance
“…Modulation of chromatin structure due to post-translational modification of histones plays a key role in establishing cell type-specific gene expression patterns and alterations of this process are involved in tumorigenesis (Flavahan et al, 2017). Frequent mutations of genes encoding for chromatin modifying enzymes and histones in multiple human cancer types further emphasize the role of perturbed epigenetic programs in tumor evolution (Feinberg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of chromatin structure due to post-translational modification of histones plays a key role in establishing cell type-specific gene expression patterns and alterations of this process are involved in tumorigenesis (Flavahan et al, 2017). Frequent mutations of genes encoding for chromatin modifying enzymes and histones in multiple human cancer types further emphasize the role of perturbed epigenetic programs in tumor evolution (Feinberg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas genotoxicity is a key determinant of carcinogenicity [77], nongenotoxic modes of action, including epigenetic effects, such as aberrant DNA methylation, histone modifications, chromatin remodeling, and micro-RNA derived modulation of gene expression, are alternative or complementary mechanisms of carcinogenesis [7886]. Future investigations are needed to determine whether e-cig vapor may exert epigenetic effects of relevance to carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that tumors exhibit both genetic and epigenetic heterogeneity within cell populations, and that epigenetic changes, such as DNA methylation and/or histone modifications, accumulate in the genome throughout oncogenesis (12)(13)(14)(15). This dynamic landscape may permit the introduction of adaptive ALK-independent mechanisms of drug resistance within targeted cells.…”
Section: Introductionmentioning
confidence: 99%
“…HDAC inhibitors may profoundly alter the activity of enhancers, the key DNA elements that regulate cell-specific gene expression, and thereby significantly influence the transcription of genes involved in the drug response (14,17,18).…”
Section: Introductionmentioning
confidence: 99%